Integrasi Model Bisnis Ekonomi Sirkular pada Persepsi Konsumen dan Keputusan Pembelian (Studi Kasus AQUA) - Grace Putlia; Hary S. Sundoro (Universitas Batanghari Jambi, 2026)
The purpose of this study is to determine consumer perceptions of companies using a circular economy business model by examining the influence of these impressions integrated into consumer perceptions and purchasing decisions. This study uses a case study design. The research sample consisted of 17 informants who were saturated samples using the snowball sampling technique. Data validity was achieved using data triangulation techniques. The results of this study revealed that the majority of informants had positive perceptions of companies using a circular economy business model. In addition, it was also found that the majority of informants stated that although perceptions and impressions of companies using a circular economy business model were positive, other main factors still apply regarding consumer products, namely brand, quality, and price.